Pengaruh Kualitas Pelayanan, Fasilitas, dan Harga terhadap Kepuasan Pasien (Studi Pada Pasien Rawat Jalan Klinik Pratama “Al-Fatah” Kabupaten Kudus) - Ifa Nur Fadlilah; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2022)
The growth and development of increasingly sophisticated science and technology resulted in intense competition in the business. Intense business competition not only occurs in businesses engaged in industry and trade, but also occurs in the field of service. One of the service sectors that are experiencing very potential development is health services. With many health facilities popping up, whether government-owned or private, it is hoped that the manager can maintain his business by providing satisfaction to patients by paying attention to several aspects, including the service quality, facilities, and prices. This research aims to determine the Effect of Service Quality, Facilities, and Prices (Case Study in Outpatients of Al Fatah Primary Clinic at Kudus Regency). The population in this study was all outpatients of Al Fatah Primary Clinic at Kudus Regency in 2017 - 2020 which amounted to 72,466 patients. Meanwhile, the number of samples used as respondents in this study amounted to 100 patients of The Primary Clinic of Al Fatah at Kudus Regency with predetermined requirements. Sampling techniques use Non Probability Sampling with purposive sampling and accidental sampling methods. Data analysis is performed using validity tests, reliability tests, correlation coefficients, determination coefficients, linear regression, and significance tests (t test and F test) using the help of SPSS 25.0 for Windows software. The test results showed that variables in the quality of service, facilities, and prices simultaneously had a positive effect on patient satisfaction with a score of 18,720 (F value) > 2,701 (F table). The advice given in this study is that managers can improve the quality of service to the maximum, increase the provision of facilities to support the performance of all employees and improve patient comfort, and readjust prices that have been set.